Is nonoperative treatment still indicated for Jones fracture? - Chee-Kidd, C.; Vivek, A.S. (2009)
Introduction: The issue of whether to treat Jones fracture surgically or nonsurgically is still controversial. In our institution, most acute Jones fractures are treated conservatively. Objectives: This study assessed the functional outcomes of patients with acute Jones fractures that were treated conservatively by means of radiographic assessment, a physician-based scoring system and patient-based questionnaires. Methodology: In this study, 25 patients with Jones fracture treated in our institution between January 2002 to December 2006, were retrospectively reviewed. Injuries were classified according to Jonesâ original description and the Torg classification. A simple patient satisfaction questionnaire was completed. Radiographic assessment of fracture union was recorded. Outcome instruments used were (a) the American Orthopaedic Foot and Ankle Society (AOFAS) clinical rating systemand (b) the American Academy of Orthopaedic Surgeons (AAOS) foot and ankle outcome questionnaire. Results: Of the 25 patients reviewed, 60 were very satisfied with the outcome, 28 were satisfied, 8 were fairly satisfied, and 4 were very dissatisfied. Based on radiographic and clinical assessments, one patient had delayed union and was treated surgically. The functional outcome scores were: mean AOFAS clinical rating score of 95.6 Â± 7.7 (P < 0.005), mean AAOS foot and ankle score of 97.0 Â± 4.4 (P < 0.005) and mean AAOS shoe comfort score of 90.2 Â± 19.6 (P < 0.005). Conclusions: Acute Jones fracture can be treated conservatively with good functional outcome.